Effectiveness of a Home Based Training Program on Caregivers Knowledge in Managing Aggressive Behavior of Patients With Mental Illness. Issue 2 (May 2022) - Lata, Kusum; Ajesh Kumar, T. K; Khakha, Deepika C.; Deep, Raman
In India, more than 90% of the patient with chronic mental illness stayed with their family members. Approximately 77.4% of caregivers experience moderate to severe levels of aggression. The purpose of this study was to evaluate the effectiveness of caregiver-training program on knowledge in managing aggressive behavior of mentally ill at home. Research design was pre-experimental. Seventy two caregivers were recruited using purposive sampling technique. The caregivers knowledge was assessed at 3 time points with regard to training program; before, immediately (post-test 1), and after 1 month (±1 week; post-test 2). The baseline knowledge was reflective of the deficiencies existing in the management of aggression of the mentally ill by caregivers. The knowledge of caregivers regarding the management of aggressive behavior of mentally ill, increased after caregiver training program, from the pre-test score of 17.63 ± 3.3 to post-test 1 score of 23.26 ± 2.9, and slightly decreased post-test 2 score of 21.01 ± 3.3 at p  < .05. Repeated measure analysis of variance (ANOVA) was done to compare the differences in knowledge score over time with Bonferroni adjustment. This home based caregiver training program helped caregivers to identify etiological factors of aggression, warning signs of aggression and use of de-escalation strategies to manage aggressive behavior of mentally ill. Training caregivers regarding aggression management will make caregiver proficient in practicing safe approach during handling of aggressive patient which will ensure the physical safety of the caregiver as well as of the patient and let the patient stay at home.